2016
DOI: 10.1007/s40256-016-0176-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Statins and the Risk of Incident Diabetes: A Retrospective Cohort Study

Abstract: Because the potential for diabetogenicity differs among different statin types, healthcare professionals should individualize statin therapy by identifying patients who would benefit more from less diabetogenic statin types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…Large scale randomized controlled trials have demonstrated that statin treatment can induce hyperglycemia and augments the risk for diabetes [15,16]. For atorvastatin and simvastatin, it has been reported that they increase the risk for diabetes in a dose-dependent manner [17,18]. In populations with high risk for type 2 diabetes, approximately 30% of the patients treated with statins developed diabetes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Large scale randomized controlled trials have demonstrated that statin treatment can induce hyperglycemia and augments the risk for diabetes [15,16]. For atorvastatin and simvastatin, it has been reported that they increase the risk for diabetes in a dose-dependent manner [17,18]. In populations with high risk for type 2 diabetes, approximately 30% of the patients treated with statins developed diabetes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of some other studies show the effect of using statin, on increasing the risk of diabetes (14,13) and increased HbA1c in patients with and without diabetes (15,16). In another study, use of statin in patients with type 1 diabetes was accompanied by increased HbA1c in these patients.…”
Section: Introductionmentioning
confidence: 89%
“…Recent meta-analyses have revealed a small but statistically significant increase in diabetes, with a number needed to harm of 225 patients (over 4 years) in one study 62 and an incidence rate of 2.2% (2 years) in another. 63 If statins induce diabetes in patients with diseases such as NASH, anticipated benefits could be negated.…”
Section: Potential Risks and Recommended Monitoringmentioning
confidence: 99%